Constituição e relação jurídica - Amaral Júnior, Aluísio Gurgel do (2006)
This study presents a reflection about the legal support given by the Federal Constitution of 1988 to the legal relations, allied to rules contained in the current private law system, valid since 11 of January of 2003, specifically the juridical relation of obligation and its essential core: the juridical link (vinculum juris). The interest in this subject relates to the teaching duty of General Theory of the Law of Obligations in the Law Course of a private university in Ceará. The general purpose of this dissertation was to analyze changes in Brazilian Legislation, which recognizing new values that fix legal precepts of the civil order, contributed to the dichotomization of concepts referring to public and private, showing human dignity as head value of legal system, as the confluence point of individual and collective interests that can not be considered antagonistic, but complementary. The methodology used in developing this study is restricted to a theoretical description on writers as Amaral (1998), Bastos (1997), Bem (2004), Betioli (1996), Beviláqua (1979), Boulos (2003), Campos (1995), Cordeiro (1980), Correia (1987), Couto e Silva (1987), Diniz (2002), Fachin (2002), Meyer (2006), Prata (1982), Reale (1973), among others. In conclusion, the juridical link (vinculum juris) that constitutes the core of obligation relations has in normativity its true characteristics; the juridical link is the rule itself and this rule has constitutional nature expressed by the Principle of Legality